Failure characteristics of UHPFRC panels subjected to projectile impact. (1st February 2020) - Beppu, M.; Kataoka, S.; Ichino, H.; Musha, H.
Abstract: This study investigates the failure characteristics of ultra-high performance fiber-reinforced concrete (UHPFRC) panels subjected to a steel projectile impact. Impact tests for 60–120-mm-thick UHPFRC panels were conducted to examine the failure state and impact resistant performance of the panels by using an 8.3-kg-mass projectile with a diameter of 90 mm at a velocity approximately corresponding to 42 m/s. Experimental parameters included the arrangement of pre-stressing steel wires and enforcement of pre-stress. Although the effect of arranging the pre-stressing steel wires on the damage restraint of UHPFRC panels was observed, the enforcement of pre-stress was not significantly effective in mitigating the damage. The impact response characteristics of UHPFRC panels were investigated by comparison between the impact force, reaction force, and strain response.